2015
DOI: 10.1038/srep14509
|View full text |Cite
|
Sign up to set email alerts
|

Small hole polaron in CdTe: Cd-vacancy revisited

Abstract: The characteristics of electronic states of Cd-vacancies in CdTe, an important semiconductor for various technological applications, are under debate both from theoretical and experimental points of view. Experimentally, the Cd-vacancy in its negative charge state is found to have C3v symmetry and a (−1/−2) transition level at 0.4 eV. Our first principles density functional calculations with hybrid functionals confirm for the first time these experimental findings. Additionally, we find that the C3v symmetry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 43 publications
(50 reference statements)
2
28
0
Order By: Relevance
“…There is evidence that the stable charge states of the Cd vacancy are negative. 1, 3 The reduction in s m with reducing temperature observed in Fig. 1 has also been observed for Cl-doped and In-doped CdTe.…”
supporting
confidence: 65%
See 3 more Smart Citations
“…There is evidence that the stable charge states of the Cd vacancy are negative. 1, 3 The reduction in s m with reducing temperature observed in Fig. 1 has also been observed for Cl-doped and In-doped CdTe.…”
supporting
confidence: 65%
“…27,30 Recent firstprinciples calculations of point defects in CdTe have provided further insight on local structure and stability. [1][2][3][4][5]31 Possible relaxed geometries of the two stable charge states, À1 and À2, of the Cd vacancy, 1,3 and for the À1 charge state of Cl-donor A-center, V Cd with a Cl Te nearest neighbor, 2 have been reported. The other point defect considered of particular importance in these materials is the Te antisite; this has also been studied and relaxed structures for the three charge states, Te þ2…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…On inclusion of more accurate theoretical treatments, like hybrid functionals, 17,18 occupation-dependent potentials, 19 and other self-interaction schemes, 20 it is seen that the coupling strength of such magnetic vacancies is too weak to explain the experimentally observed FM ordering. It is because they observed that the holes are more localized at the defect sites than predicted by the local and semilocal functionals.…”
Section: Introductionmentioning
confidence: 99%